2021
DOI: 10.1017/s1368980021003347
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency: experience from a tertiary referral UK hospital; not just a low- and middle-income country issue

Abstract: Objective: Vitamin A (VA) deficiency, more common in low- and middle-income countries (LMIC) secondary to malnutrition, is associated with increased morbidity and mortality. The prevalence and impact of VA deficiency in high-income countries (HIC) where chronic conditions may predispose is less well understood. Setting: We examined the scale of low and deficient VA status in our tertiary University Teaching Hospital (HIC). Participants: Patients undergoing serum retinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In the meantime, a recent study has been published recently, showing that vitamin A deficiency is not unique to underdeveloped countries, but can also be seen in developed western societies (100). This study also emphasized the relationship between vitamin A deficiency and inflammation (100).…”
Section: Covid-19 Chronic Diseases and Vitamin A Deficiency: A Brief ...mentioning
confidence: 84%
See 1 more Smart Citation
“…In the meantime, a recent study has been published recently, showing that vitamin A deficiency is not unique to underdeveloped countries, but can also be seen in developed western societies (100). This study also emphasized the relationship between vitamin A deficiency and inflammation (100).…”
Section: Covid-19 Chronic Diseases and Vitamin A Deficiency: A Brief ...mentioning
confidence: 84%
“…Vitamin A deficiency is the main reason behind chronic diseases, which is seen as the most important reason why COVID-19 hits big metropolises more than rural areas. The relationship between vitamin A deficiency and inflammation and chronic disease has been shown in many studies (100,101,102,103) The main reason behind obesity, diabetes, cardiovascular diseases, and many other chronic inflammatory diseases that cause comorbidity for COVID-19 is nutrition with low nutritional value, western style, high calorie packaged foods (104,105,106). Healthy-eating adults have a lower risk of obesity, heart disease, type 2 diabetes, and cancer, and they live longer (107).…”
Section: Covid-19 Chronic Diseases and Vitamin A Deficiency: A Brief ...mentioning
confidence: 99%
“…Vitamin A has roles in growth, and in the prevention of night blindness [ 64 ] and reduced vitamin A status increases the risk of infection [ 65 ]. Marley et al (2021) recently demonstrated that in patients replete or having abnormal levels of vitamin A have increased rates of inflammation and C-reactive protein [ 66 ]. This study pointing to an important role of vitamin A in mitigating rates of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical vitamin A deficiency is linked to a worsened outcome and disease course and is closely linked to iron deficiency and to inflammation (156)(157)(158). Retinol is mobilized from the liver by an iron-dependent enzyme (159), with irondeficient conditions hindering the mobilization of this vitamin.…”
Section: Vitamin Amentioning
confidence: 99%